Efek Antihipertensi dan Hipotensi beberapa Fraksi dari Ekstrak Etanol Umbi Lapis Kucai (Allium schoenoprasum L., Lliliaceae) - Irda Fidrianny; Kosasih Padmawinata; Soediro Soetarno; Elin Yulinah (Institut Teknologi Bandung, 2003)
Hypotensive and antihypertensive effect of fractions of ethanolic extract of âkucaiâ (Allium schoenoprasum L., Liliaceae) bulb had been tested on male Wistar rats. The ethyl acetate, n-buthanol and aqueous fractions of both fresh and dry bulb had hypotensive and antihypertensive effects. The aqueous fraction of fresh bulb at a dose of 25 mg/kg body weight showed the highest hypotensive and antihypertensive activities. The n-buthanol fraction of dry bulb at a dose of 50 mg/kg body weight showed the highest hypotensive activity. The ethyl acetate fraction of dry bulb at a dose of 50 mg/kg body weight showed the highest antihypertensive activity.